2010
DOI: 10.1007/s00011-010-0166-8
|View full text |Cite
|
Sign up to set email alerts
|

Urinary trypsin inhibitor suppresses excessive generation of superoxide anion radical, systemic inflammation, oxidative stress, and endothelial injury in endotoxemic rats

Abstract: UTI suppressed excessive O(2)(-*) generation, systemic inflammation, lipid peroxidation, and endothelial injury in endotoxemic rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 46 publications
0
27
0
Order By: Relevance
“…In addition, previous studies have demonstrated that UTI suppresses the elevation of IL-6 and IL-8 levels in patients undergoing coronary artery bypass grafting under extracorporeal circulation (18), alleviates forebrain I/R injury by inhibiting the production of superoxide radicals and intercellular adhesion molecule-1 (19) and improves oleic acid-induced acute lung injury by reducing TNF-α levels and inducing leukocyte activation (20). In addition, UTI has been proposed as a therapeutic option for endotoxin-associated inflammatory disorders, including acute lung and liver injuries (21), due to its anti-inflammatory properties (22)(23)(24). However, whether UTI protects against brain injury by inhibiting the inflammatory responses following CA is yet to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, previous studies have demonstrated that UTI suppresses the elevation of IL-6 and IL-8 levels in patients undergoing coronary artery bypass grafting under extracorporeal circulation (18), alleviates forebrain I/R injury by inhibiting the production of superoxide radicals and intercellular adhesion molecule-1 (19) and improves oleic acid-induced acute lung injury by reducing TNF-α levels and inducing leukocyte activation (20). In addition, UTI has been proposed as a therapeutic option for endotoxin-associated inflammatory disorders, including acute lung and liver injuries (21), due to its anti-inflammatory properties (22)(23)(24). However, whether UTI protects against brain injury by inhibiting the inflammatory responses following CA is yet to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Kobayashi et al observed that UTI inhibited tumor invasion and metastasis, possibly through the suppression of cell-associated plasmin activity and the mRNA and protein expression of urokinase plasminogen (uPA). In endotoxemic rats, UTI suppresses excessive superoxide (O 2 -) generation, systemic inflammation, lipid peroxidation and HMGB1 (33). However, the potential role of UTI in the regulation of HMGB1 in cancer remains to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Following activating of macrophage, neutrophils, NADPH oxidase is activated, leading to excessive ROS generation to kill the bacteria. Of course, one coin two sides, at the sometime ROS also injuries lung tissue and lead to breathlessness, and then enhance SIRS (Tanaka et al 2010). Japanese scholars found out the level of O 2 -, HMGB1, TNF-a, IL-6 were lower in UTI treatment group than the control group (Tanaka et al 2010).…”
Section: Decrease the Production Of Omentioning
confidence: 99%
“…Of course, one coin two sides, at the sometime ROS also injuries lung tissue and lead to breathlessness, and then enhance SIRS (Tanaka et al 2010). Japanese scholars found out the level of O 2 -, HMGB1, TNF-a, IL-6 were lower in UTI treatment group than the control group (Tanaka et al 2010). Previous studies had shown that the expression of HMGB1, TNF-a, IL-6 was regulated by NF-κB.…”
Section: Decrease the Production Of Omentioning
confidence: 99%